Graphic-Semantic Expressions Map: A New Tool on Design Teaching - Rijo, Cátia (2020)
This paper aims to contribute to the discussion in design teaching and its consequent research context, considering participatory practices and methodologies. We propose a methodologic map, which will assist the process of synthesis expressive code and also boost the relationship between graphic expression and semantics in design practice. At the end, an attempt is made to evaluate if the association of semantic elements with graphic elements promote the convergence between the project goals and the synthesis of expressive codes, while facilitating the interpretation and creation of new graphic products.